Efecto de quitosano, hongos micorrízicos y ácidos húmicos sobre el crecimiento y desarrollo en variedades de pimiento (Capcicum annuum L) bajo condiciones protegidas. - Solórzano Cedeño, Arturo Enedicto (2019)
The purpose of this research was to evaluate the effect of chitosan, mycorrhizal fungi and humic acids on the growth and development of pepper varieties under protected conditions. The trial was carried out in the experimental farm "La María" in the cantón Mocache, provincia, Los Ríos Province, located at kilometer 7.5 of the Quevedo-El Empalme road. A completely randomized design with 2x4 factorial arrangement was used in 3 repetitions, the first factor was the varieties (Magaly and Lycal), and the second the biostimulants: humic acids (1:30 v/v), chitosan (3 g/l of water) and mycorrhizal fungi (20g of spores/ml), adding one control (control) for each variety (without bioactive application). The results showed that the three bioactives studied increased the germination of the seeds between 11.66 and 16.67%, while the emergency was enhanced by humic acids and chitosan (90.00 and 86.67% of seedlings emerged, reactively). The application of humic acids produced plants of greater height at 25 and 45 days after sowing with 19.38 and 46.38 cm, and stems of greater diameter 8.87 and 16.05 mm, in the two evaluations, respectively. This in turn increased the fresh and dry biomass of the seedlings (339.38 and 106.72 g). The production of fruits per plant (15.33 fruits), as well as their characteristics of length, diameter and weight were increased by applying humic acids (12.22 cm, 43.33 mm and 92.22 g), generating the highest yield with 29166.67 kg / ha. The Magaly variety significantly exceeded the Lycal variety in terms of germination (96.67%), emergency (95.00%), plant height and stem diameter (18.67 and 8.34 at 25 days after sowing and 46.38 cm and 14.68 mm a 45 days after sowing), as well as fresh and dried biomass (290.60 and 89.65 g). The yield expressed in fruits per plant was higher in the Magaly variety with 13.42 fruits, the same ones that presented greater length (11.18 cm), diameter (40.67 mm) and weight (81.07 g), components that also reflected the highest yield (22916.67 kg /he has). Keywords: pepper cultivation, bioactive, horticultural production